BIOCHRONOLOGY OF SELECTED MAMMALS, MOLLUSCS AND OSTRACODS FROM THE MIDDLE PLIOCENE TO THE LATE PLEISTOCENE IN ITALY. THE STATE OF THE ART (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
The Authors have elaborated four range charts of mammalian (large and micro), molluscs and fresh-water and brackish ostracodes faunas, for the selected Plio-Pleistocene fossiliferous localities of the Italy. A new Mammal Age (Aurelian) correlatable to late Middle and Late Pleistocene has been defined. Inside this age two Faunal Units (Torre in Pietra and Vitinia) have been defined as characteristic for Early and Middle Aurelian, while no gisements have been chosen for the late Aurelian. Biochronological units are calibrated on magnetostratigraphic and isotopic scales and by radiometric datings.